Effects of low-concentrations of simazine on early life stages of common carp (Cyprinus carpio L.) - Velisek, Josef; Stara, Alzbeta; Machova, Jana; Dvorak, Petr; Zuskova, Eliska; Svobodova, Zdenka (Neuro endocrinology letters, 2012)
OBJECTIVES: The aim of this study is to assess the toxicity of simazine in different developmental stages of common carp (Cyprinus carpio) on the basis of mortality, early ontogeny, occurrence of morphological anomalies, growth rate, and Fulton's condition factor during and at the conclusion of the test. DESIGN: The toxicity tests were performed on carp according to OECD 210 methodologies. The developmental stages of carp were exposed to simazine at four concentrations, 0.06, (reported concentration in Czech rivers), 60, 600, and 3000 µg/l for 36 days and compared to carp in a non-treated control group. RESULTS: Simazine in concentration 0.06 µg/l had no effect on early life stages of carp. Simazine in concentration 600 and 3000 µg/l caused decrease of mass and total length of carp. Fish exposed to three highest levels of simazine showed alteration of tubular system of caudal kidney. On the basis of histopatological changes the values of LOEC = 60 µg/l, NOEC = 0.06 µg/l for simazine were estimated. CONCLUSIONS: Chronic simazine exposure of early-life stages of common carp affected their growth rate, and histology. Some of the changes were observed only at higher exposures (600, 3000 µg/l), but change founded in caudal kidney was affected in fish exposed to the second lowest concentration tested (i.e., 60 µg/l), which is about 10 µg/l higher than reported in Colorado rivers in recent years. Concentrations of simazine in World rivers have been reported to generally vary in the range 0.0003-49.20 µg/l.
Keywords: Simazine; chemické látky znečišťující vodu; Embryo, Nonmammalian; Ovum; ovum; Male; Česká republika; řeky; vztah mezi dávkou a účinkem léčiva; Kidney; Water Pollutants, Chemical; kapři; mužské pohlaví; Rivers; Herbicides; Models, Biological; Czech Republic; simazin; Animals; biologické modely; ženské pohlaví; Toxicity Tests; ledviny; zvířata; testy toxicity; Carps; herbicidy; Female; Dose-Response Relationship, Drug; embryo nesavčí